Organizational factors, ambidextrous innovation, absorptive capacity, and a firm’s green competitive advantage - Baquero, Asier (Management Decision, 2025)
Purpose: This study aims to investigate the effect of organizational factors (green transformational leadership [GTL] and green knowledge management [GKM]) on a firm's green competitive advantage (GCA). Additionally, the study examines the role of ambidextrous green innovation (GI) as a mediator and green absorptive capacity (GAC) as a moderator in this relationship. The study also explores the multiple pathways leading to enhanced GCA using a configurational approach. Design/Methodology/Approach: A cross-sectional approach was used to collect primary data from manufacturing and service firms in the UAE. Structural Equation Modeling (SEM) and Fuzzy-set Qualitative Comparative Analysis (fsQCA) were used for analysis. Findings: The study found that GTL and GKM have a significant direct effect on GCA, as well as significantly impact exploitative and exploratory GI. EIGI and ERGI were found to mediate the associations between GTL/GKM and GCA significantly. Interestingly, GAC was found to have a significant impact on the GKM-ERGI relationship. Additionally, the study revealed four solutions with different combinations of configurations leading to improved GCA. Practical implications – The study provides valuable insights for policymakers and executives in developed countries to enhance their organizations' GCA through the establishment of green strategic factors and stimulation of ambidextrous GI. Originality/Value: This research contributes to bridging research gaps in the literature and advances our understanding of the interrelationship between organizational factors, ambidextrous GI, GAC, and GCA. Additionally, the study offers methodological significance by combining direct and configurational techniques to address these research gaps.
Keywords: green transformational leadership; green knowledge management; ambidextrous green innovation; green absorptive capacity; green competitive advantage